Advances in the formal cycloadddition reaction between enolisable anhydrides and electrophiles - (:unkn) unknown (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
Expansion of the scope of catalytic cycloaddition reactions involving enolisable anhydrides to various Michael acceptors as electrophiles has been investigated. The reaction between homophthalic anhydrides and α-β; unsaturated carbonyl compounds under mild conditions has furnished dihydroisocoumarin products bearing 3 stereocentres (one being quaternary) in good yield, excellent diastereoselectivity, however with poor enantiocontrol. Efforts were exhausted in the development of optimal catalytic conditions for this reaction and as such it was deemed impossible to achieve good stereocontrol without being able to reduce the rate of uncatalysed background reaction. A novel reaction in which a racemic α-branched aldehyde is kinetically resolved by bifunctional cinchona alkaloid derived organocatalysts while simultaneously forming 3 stereocentre-containing dihydroisocoumarin acids with good diastereoselectivity and excellent enantiocontrol is also reported. Testing of various aldehydes in this reaction showed that the use of alkyl substituted α-branched aldehydes in the presence of bifunctional cinchona alkaloid-derived organocatalyst bearing a bulky aromatic substituent furnished good levels of dr and ee. Inspired by the success of the first catalytic asymmetric cycloaddition reaction between aldehydes and homophthalic anhydrides an investigation into the possibility of reversing the high levels of trans-diastereoselectivity previously observed was carried out by choice of a bulky substituted squaramide-based catalyst. This process provided one pot access to functionalised cis-dihydroisocoumarins in high yields and excellent optical purity- products which are recognised as privileged core structures in natural compounds with diverse pharmacological activities. In order to rationalise the stereochemical outcome, computational studies in support of the experimental data were carried out by a collaborator. The methodology developed was later extended to the use of aryl succinic anhydrides as a means of accessing paraconic acid derivatives (another privileged core present in natural products exhibiting a broad spectrum of biological activity) in a highly enantioselective fashion. The catalytic asymmetric cycloaddition between phenyl glutaconic anhydride and hindered branched aldehydes was also explored. The results obtained demonstrated the feasibility of the process which allows for the synthesis of 3,4-dihydropyrone derivatives bearing two stereocentres as potential precursors to natural products of the kavalactone family. Finally, the synthesis and employment of bifunctional iminophosphorane catalysts in formal cycloaddition reactions involving less reactive anhydrides and aldehydes was examined. The catalytic cycloaddition between phenyl glutaconic anhydride and aromatic aldehydes was made possible for the first time, and further optimisation of the cycloaddition with aliphatic aldehydes is also reported.
APPROVED